A Comparison of The Approach of Ottoman Provincial Administrators to The Tanzimat Reforms: The Attitudes of The GovernorsThe Province of Erzurum and The Erzurum Civil Service of Mehmet Kâmi?l Pasha (1839-1846) - Toraman, Ömer (Fırat University, 2023)
Erzurum province, one of the provinces far from the capital, was included in the Tanzimat in 1845. From 1839 to 1845, Halil Kâmilî Pasha, one of the governors of Erzurum province, opposed the implementation of the military provisions of the Tanzimat in this province, and resigned from his post when he could not achieve any results. Thus, the instruction prepared to be sent to him regarding the implementation of the Tanzimat provisions in all its aspects remained unaddressed. Although his successor Bekir Sami Pasha made efforts to implement the Tanzimat provisions, he was deemed unsuccessful by the Majlis-i Vâlâ and the Sadaret as a result of his inexperience in the face of the location and size of the province and the difficulties encountered in Van, Muş and Çıldır Sanjaks. Mehmet Kâmil Pasha, a member of the Majlis-i Vâlâ, was sent to Erzurum on a special mission to identify and solve the problems in the province. Mehmet Kamil Pasha took important steps in the implementation of Tanzimat provisions. Bekir Sami Pasha was dismissed due to his inexperience, and Esat Muhlis Pasha, who had previously served as governor of Erzurum, was appointed governor of Erzurum for the second time. Esat Muhlis Pasha continued the activities initiated by Mehmet Kamil Pasha and worked for the implementation of Tanzimat provisions in all aspects. The difficulties encountered especially in the Sanjaks of Van, Muş and Çıldır were not fully resolved during Esat Muhlis Pasha's term and continued to be on the agenda of his successor governors. The expectations of the reformist group at the center in the implementation of the Tanzimat provisions could not be fully met due to the attitudes of anti-reform governors and the practices of inexperienced governors.

Başkente uzak eyaletlerden olan Erzurum eyaleti 1845 yılında Tanzimat’a dâhil edildi. 1839 yılından, 1845 yılına kadar, Erzurum eyaleti valiliği görevini yürütenlerden Halil Kâmilî Paşa, Tanzimat’ın askeri hükümlerinin bu eyalette uygulanmasına karşı çıkmış, netice alamayınca görevinden istifa etmiştir. Böylece Tanzimat hükümlerinin, bütün yönleri ile uygulanması konusunda kendisine gönderilmek üzere hazırlanan talimat muhatapsız kalmıştır. Halefi Bekir Sami Paşa, Tanzimat hükümlerinin uygulanması için gayret gösterdi ise de eyaletin konumu, büyüklüğü, Van, Muş ve Çıldır sancaklarında karşılaşılan güçlükler karşısında, tecrübesizliğinin bir neticesi olarak Meclis-i Vâlâ ve Sadaret tarafından başarısız bulundu. Eyalet genelinde sorunların tespiti ve çözümü için, Meclis-i Vâlâ azası Mehmet Kâmil Paşa özel görevle Erzurum’a gönderildi. Mehmet Kâmil Paşa Tanzimat hükümlerinin uygulanması hususunda önemli adımlar attı. Tecrübesizliği sebebiyle görevden alınan Bekir Sami Paşa’nın yerine, daha önce Erzurum valiliği görevini yürütmüş olan, Esat Muhlis Paşa ikinci defa Erzurum valisi olarak atandı. Esat Muhlis Paşa, Mehmet Kâmil Paşa’nın başlatmış olduğu faaliyetleri devam ettirmiş, Tanzimat hükümlerinin bütün yönleri ile uygulanması için çalışmıştır. Özellikle Van, Muş ve Çıldır sancaklarında karşılaşılan güçlükler, Esat Muhlis Paşa’nın döneminde tam olarak çözülememiş, halefi valilerin de gündeminde olmaya devam etmiştir. Tanzimat hükümlerinin uygulanmasında merkezdeki reformcu grubun beklentisi, reform karşıtı valilerin tutumları ve tecrübesiz valilerin uygulamaları nedeniyle, tam olarak karşılanamamıştır.
OSMANLI TAŞRA YÖNETİCİLERİNİN TANZİMAT REFORMLARINA YAKLAŞIMINA DAİR BİR MUKAYESE: ERZURUM EYALETİ VALİLERİNİN TUTUMLARI VE MEHMET KÂMİL PAŞA’NIN ERZURUM MEMURİYETİ (1839-1846)
Keywords: Historical; Comparative and Typological Linguistics; Tarihsel; Karşılaştırmalı ve Biçimsel Dilbilim